The benefits and challenges of online professional-patient interaction: Comparing views between users and health professional moderators in an online health community. (June 2018) - Atanasova, Sara; Kamin, Tanja; Petrič, Gregor
Abstract: Online health communities (OHCs) have become new venues for online professional-patient interactions in which patients, as OHC users, can undertake online consultations with health professional moderators. This interaction has previously been investigated mainly from the user's perspective, whilst neglecting the insights of health professional moderators. The aim of this study is to explore and compare the benefits and challenges of online professional-patient interactions for users and health professional moderators and the effects on face-to-face medical encounters. The study employed a qualitative research design, with in-depth, semi-structured interviews conducted with users ( n  = 8) and health professional moderators ( n  = 7) from the largest OHC in Slovenia. Data analysis utilised inductive thematic analysis and principles of grounded theory. The results of this small study demonstrate that the OHC enabled users and health professional moderators to overcome weaknesses of face-to-face medical encounters. Both users and professionals view the primary benefits of online professional-patient interaction as delivering informational and emotional support for users' health-related needs. The main challenges for users and health professional moderators stem from the limitations of computer-mediated communication (CMC). Users and health professional moderators expressed different and ambivalent attitudes toward the OHC and its effect on face-to-face medical encounters. Highlights: Online professional-patient interaction benefits pertain to online social support. OHC users see the main benefits in receiving informational online social support. Health professional moderators view benefits in addressing users' health needs. Online professional-patient interaction challenges stem from limitations of CMC. Interactions in OHCs can overcome weaknesses of face-to-face medical encounters.